2017
DOI: 10.31234/osf.io/kp3fg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Workplace Accommodations for Employees with Disabilities: A Multilevel Model of Employer Decision-Making

Abstract: Purpose: Existing research suggests that the decision to grant or deny workplace accommodations for people with disabilities is influenced by a range of legal and non-legal factors. However, less is known about how these factors operate at the within-person level. Thus, we proposed and tested a multilevel model of the accommodation decision-making process, which we applied to better understand why people with psychological disabilities often experience greater challenges in obtaining accommodations. Method: A … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Over-reliance on heuristical guidance must be addressed by the research communities, and requires collaboration within applied psychological sub-disciplines, occupational therapy, occupational medicine and human resources departments. The limited evidence that does exist broadly supports the implementation of adjustments 64 , 74 , 77 , 80 , 81 but, without sophistication, we are unable to speak to quality control, return on investment or predict which type will work for different individuals/roles. Intensive personalized employment support (IPS) such as that provided to autistic people with multiple needs and people with moderate mental health conditions have found that the benefits only outweigh the costs when wider community measures such as housing and health costs are factored in.…”
Section: Occupational Considerations Of Neurodiversitymentioning
confidence: 94%
“…Over-reliance on heuristical guidance must be addressed by the research communities, and requires collaboration within applied psychological sub-disciplines, occupational therapy, occupational medicine and human resources departments. The limited evidence that does exist broadly supports the implementation of adjustments 64 , 74 , 77 , 80 , 81 but, without sophistication, we are unable to speak to quality control, return on investment or predict which type will work for different individuals/roles. Intensive personalized employment support (IPS) such as that provided to autistic people with multiple needs and people with moderate mental health conditions have found that the benefits only outweigh the costs when wider community measures such as housing and health costs are factored in.…”
Section: Occupational Considerations Of Neurodiversitymentioning
confidence: 94%
“…Other studies show that organizational processes for requesting accommodations vary and are associated with accommodation requests and provision. Among employees with disabilities, perceptions of organizational reasonableness and a climate of inclusion likely influence accommodation provision [45,53]. Studies also suggest that accommodation requests from employees with psychological disabilities, and generally hidden disabilities, often are perceived by employers as less reasonable, and as such are less likely to be granted [45,54].…”
Section: Prior Research On Workplace Accommodationsmentioning
confidence: 99%